The Effect of Geoboard Media on the Skill of Understanding Two-Dimentional Figure on Children with Vision Impairments - Sumardi Sumardi; Sima Mulyadi (UPI Kampus Cibiru, 2022)
This study aims to determine the effect of using geoboard media on the understanding of two-dimentional figure for children who have visual impairments in the inclusion class of SLB Aisyiah Singaparna. The research approach used in this study is a quantitative approach with the Single Subject Research method and the A-B-A research design. The subjects in this study were students who had visual impairment at the early childhood level with the initials FSS who had difficulty understanding the concept of two-dimentional figure. The results of this study indicate that the mean FSS level at the baseline-1 stage (A-1) is 55.2%, then at the intervention stage (B) the mean FSS level has increased to 78.1% and the mean level in the baseline-2 phase (A-2) to 91.0%. As for the results of the analysis in conditions, it was found that the geoboard media had a positive influence where this was shown in the estimation of the direction of the trend, the trend of stability, the data trail, the level of stability and range, and the level of data change. Likewise with the analysis between conditions, it is described in the number of variables that are changed, changes in direction and effects, trends in stability, changes in levels, and data overlap. Based on these results, it can be concluded that geoboard media can be used as a medium to improve understanding of two-dimentional figure for students who have visual impairments at the early childhood level in the Aisyiah Singaparna SLB inclusion class